Caractéristiques d’un dispositif hybride de formation continue pour les accompagnateurs d’enseignants stagiaires en enseignement professionnel - Gagné, Andréanne; Petit, Matthieu (Revue internationale des technologies en pédagogie universitaire, 2021)
In an effort to support trainees in teaching during their internship, the programs of Quebec universities develop continuous education targeted at mentors. There has been little research pertaining to this training offer to these key players in practice settings, much less on the growing role of hybrid training in the vocational education sector. Data were collected through 16 semi-structured interviews and subjected to an inductive analysis process. Such data allowed to further define the training needs of the studied population. This article highlights characteristics related to mediation and mediatization to meet the needs of interactions, authenticity and accessibility of mentors.